Naphthalene (NAPH) signals from PVC and other synthetic polymers - Isabel Goßmann; Corinna Wirth; Barbara M. Scholz-Böttcher (PANGAEA, 2025)
This excel file contains information about the generation of naphthalene (NAPH) from PVC and other synthetic polymers when analyzed with Py-GC/MS.
In: Goßmann, I et al. (2025): Pyrolysis-GC/MS Reference Data for Polymeric and Refractory Materials to Evaluate C-PVC Indicator Specificity [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984614